Cosmic variance and the inhomogeneous UV luminosity function of galaxies during reionization - Dawoodbhoy, Taha; Shapiro, Paul R; Ocvirk, Pierre; Lewis, Joseph; Aubert, Dominique; Sorce, Jenny G; Ahn, Kyungjin; Iliev, Ilian T; Park, Hyunbae; Teyssier, Romain; Yepes, Gustavo (Monthly notices of the Royal Astronomical Society, 2023)
When the first galaxies formed and starlight escaped into the intergalactic medium to reionize it, galaxy formation and reionization were both highly inhomogeneous in time and space, and fully coupled by mutual feedback. To show how this imprinted the UV luminosity function (UVLF) of reionization-era galaxies, we use our large-scale, radiation-hydrodynamics simulation CoDa II to derive the time- and space-varying halo mass function and UVLF, from z ≃ 6-15. That UVLF correlates strongly with local reionization redshift: earlier-reionizing regions have UVLFs that are higher, more extended to brighter magnitudes, and flatter at the faint end than later-reionizing regions observed at the same z. In general, as a region reionizes, the faint-end slope of its local UVLF flattens, and, by z = 6 (when reionization ended), the global UVLF, too, exhibits a flattened faint-end slope, ‘rolling-over’ at MUV ≳ −17. CoDa II’s UVLF is broadly consistent with cluster-lensed galaxy observations of the Hubble Frontier Fields at z = 6-8, including the faint end, except for the faintest data point at z = 6, based on one galaxy at MUV = −12.5. According to CoDa II, the probability of observing the latter is $\sim 5~{{\ \rm per\ cent}}$. However, the effective volume searched at this magnitude is very small, and is thus subject to significant cosmic variance. We find that previous methods adopted to calculate the uncertainty due to cosmic variance underestimated it on such small scales by a factor of 2-4, primarily by underestimating the variance in halo abundance when the sample volume is small.